Rethinking Juan Luis Segundo: Phenomenological Philosophy, Existentialism and Liberation Theology - Marlon Christian Tirayoh; Jeni Kistisia; Maya Permata Sinta; Sella Vinisya; Aprianto Wirawan; Alfonso Munte (Westscience Press, 2023)
Based on the research, this study aims to reflect the thought of Juan Luis Segundo, a theology-oriented scholar and philosopher whose style of thought itself is not far from phenomenological and existentialist philosophical analysis tools for the development of theology, although this philosophy basically needs to get attention when it encounters contexts (global, regional, national to local) in religion, culture, and social circles. Based on this research, this study is conducted as qualitative research with data retrieval techniques through secondary sources. Secondary sources include the selection of relevant journals, recent or originating from the last 10 years which encounter the reality of theology and thought patterned on phenomenological-existentialist philosophy on theology that favors orthodoxy rather than orthopraxy. Results have shown that the introduction of orthopraxis as foothold of theology without neglecting orthodoxy is crucial in order to determine the extent to which phenomenology is further existentialized even though it clashes with the era and/or generation.